Thoughts about health and patient-reported outcomes among people with diabetes mellitus: results from the DiaDec-study - Sandra O. Borgmann; Nadja Chernyak; Burkhard Haastert; Ute Linnenkamp; Silke Andrich; Rabea Schlenker; Oliver Razum; Andrea Icks (BMC, 2021)
Abstract Background There is considerable evidence that repetitive negative thoughts are often associated with adverse health outcomes. The study aims are (i) to identify the frequency and valence of thoughts about health in people with diabetes mellitus using questions based on the day reconstruction method (DRM) and (ii) to analyse associations between thoughts about health and health-related quality of life (HRQoL), diabetes-related distress and depressive symptoms. Methods Cross-sectional study of a random sample of a German statutory health insurance population with diabetes aged between 18 and 80 linking questionnaire and claims data. Associations between frequency and valence of thoughts about health on a previous day and HRQoL assessed by a 12-Item Short-Form Health Survey, diabetes-related distress assessed using the Problem Areas in Diabetes scale and depressive symptoms assessed by Patient Health Questionnaire-9 were analysed using linear and logistic regression analysis, adjusting for sociodemographic and clinical characteristics. Results Thoughts about health were analysed in 726 participants (86% type 2 diabetes, 62% male, mean age 67.6 ± 9.7 years). A total of 46% had not thought about their health the day before, 17.1% reported low frequency and negative thoughts, 21.4% low frequency and positive thoughts, 12.1% high frequency and negative thoughts and 3.4% high frequency and positive thoughts. The presence of thoughts about health irrespective of their frequency and valence is associated with a lower physical and mental component summary score of the 12-Item Short-Form Health Survey. Negative thoughts are associated with high diabetes-related distress. Frequent or negative thoughts are associated with depressive symptoms. Conclusions Thoughts about health are a part of everyday life for a substantial number of people with diabetes. Surprisingly, even positive thoughts are associated with poorer HRQoL in our study. Further research within the DRM paradigm is needed to understand how thoughts about health may affect people's (assessment of) state of health. Thoughts about health should be considered in diabetes education and patient counselling with a view to preventing and treating emotional disorders. More attention should be paid to the outcomes of interventions that may themselves lead to an increase in the frequency of thoughts about health.